2014
DOI: 10.1007/s13277-014-2501-0
|View full text |Cite
|
Sign up to set email alerts
|

A triterpenoid saponin from Adenophora triphylla var. japonica suppresses the growth of human gastric cancer cells via regulation of apoptosis and autophagy

Abstract: In the present study, we investigated the effects of 3-O-β-D-galactopyranosyl-(1 → 2)-[β-D-xylopyranosyl-(1 → 3)]-β-D-glucuronopyranosyl-28-O-[α-L-arabinopyranosyl-(1 → 4)-α-L-arabinopyranosyl-(1 → 3)-β-D-xylopyranosyl-(1 → 4)-α-L-rhamnopyranosyl-(1 → 2)-β-D-fucopyranosyl] quillaic acid, named compound 1, on the induction of apoptosis and autophagy in human gastric cancer AGS cells. Compound 1, a triterpenoid saponin isolated from the root of Adenophora triphylla var. japonica, effectively inhibited the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Because of their apparently safety and efficacy, triterpenoid saponins have been gaining increasing interest for cancer therapy ( Du et al, 2014 ; Singh et al, 2017 ). The anticancer triterpenoid saponins modulate numerous signaling targets related to angiogenesis, apoptosis, autophagy, cancer stem cells, inflammation, metastasis, microRNAs, multidrug resistance, proliferation, and oxidative stress ( Liu et al, 2013 ; Cheng et al, 2014 ; Chun et al, 2014 ; Du et al, 2014 ). Our previous studies have shown that Platycodin D (PD), another triterpenoid saponin, has potent activity against prostate ( Zhou et al, 2015 ) and breast/mammary gland ( Kong et al, 2016 ) cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of their apparently safety and efficacy, triterpenoid saponins have been gaining increasing interest for cancer therapy ( Du et al, 2014 ; Singh et al, 2017 ). The anticancer triterpenoid saponins modulate numerous signaling targets related to angiogenesis, apoptosis, autophagy, cancer stem cells, inflammation, metastasis, microRNAs, multidrug resistance, proliferation, and oxidative stress ( Liu et al, 2013 ; Cheng et al, 2014 ; Chun et al, 2014 ; Du et al, 2014 ). Our previous studies have shown that Platycodin D (PD), another triterpenoid saponin, has potent activity against prostate ( Zhou et al, 2015 ) and breast/mammary gland ( Kong et al, 2016 ) cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Natural products have provided an invaluable source of therapeutic agents, especially for anticancer drug discovery. Terpenoid saponins, including the triterpenoid saponins and diterpenoid saponins identified from many herbs, have been demonstrated to have activity against human cancer cells ( Haridas et al, 2001 ; Mujoo et al, 2001 ; Liu et al, 2013 ; Cheng et al, 2014 ; Chun et al, 2014 ; Du et al, 2014 ; Zhou et al, 2015 ; Singh et al, 2017 ). We recently examined four triterpenoid saponins and one diterpenoid saponin for their antitumor effects against androgen-independent PC3 prostate cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of p16 and the increased number of β -gal staining cells supported the evidence that sinocrassulosides VI/VII induced senescence in HeLa cells. Triterpenoid saponins have been proven as potential antitumor agents, due to their ability to induce apoptosis in cancer cells [27, 28]. We are the first to demonstrate that oleanane-type triterpenoid saponin from S. viscidula may inhibit cell proliferation by inducing cell cycle arrest and senescence besides the reported apoptosis mechanism.…”
Section: Discussionmentioning
confidence: 88%
“…Therapeutic agents in gastrointestinal cancer are summarized in Tables 1 and 2 [46][47][48][49][50][51][52][53][54][55][56][57].…”
Section: Autophagy As a Therapeutic Target In Gastrointestinal Carcinmentioning
confidence: 99%